Майко В.В. Кырк-Ерский клад городища Чуфут-Кале в Юго-Западном Крыму - Чореф, М.М. (Археологія, 2009)
Рецензия на книгу: Кырк-Ерский клад городища Чуфут-Кале в Юго-Западном Крыму К.: Академпериодика, 2007. — 190 с.